Strategi Unit Pelaksana Teknis (UPT) Museum Daerah Nusa Tenggara Timur (NTT) dalam Meningkatkan Pelayanan Publik - Robertus Edward Gandur; David B.W. Pandie; Alfred Omri Ena Mau; Yaherlof Foeh (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to analyze the strategy of the NTT Regional Museum UPT in improving public services. The problem behind this research is that the quality of museum services has not been optimal, which can be seen from the lack of a target number of visitors and the limited innovation of technology-based services. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through interviews, observations, and documentation, then analyzed through data reduction, data presentation, and conclusion drawn. The results of the study show that the service strategy of the NTT Regional Museum UPT can be analyzed based on five strategies according to David Osborne and Peter Plastrik (in the book: Cutting Bureaucracy Five Strategies Towards Entrepreneurial Government (2020)), namely core strategy, consequence strategy, customer strategy, control strategy, and cultural strategy. The core strategy has been clearly formulated according to the Strategic Plan, but its implementation is not optimal. The consequence strategy still focuses on administrative discipline and is not yet based on service quality. Customer strategies have been implemented through various programs, but they are still conventional and have not made the most of technology. The control strategy emphasizes more on procedural compliance, while the work culture shows discipline, but service innovation still needs to be improved. In conclusion, the service strategy has been running, but it needs to be strengthened in implementation, innovation, and performance evaluation so that museum services are more effective and in accordance with the needs of the community.